Analisis Nilai-Nilai Al-Qur’an terhadap Tradisi Assimellereng dalam Konteks Moderasi Beragama di Masyarakat Bugis (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
This research analyzes the values of the Qur'an in the assimellereng tradition in the Bugis community in relation to Religious Moderation. Assimellereng is a concept of love, togetherness, and unity in the Bugis community to overcome tensions and inter-religious conflicts. This research uses a qualitative method with a review of the Qur'an approach. The main findings show that assimellereng and the teachings of the Qur'an are closely related in building a harmonious and tolerant society. The values of assimellereng, such as sipakatau, sipakalebbi, and sipakainge', align with the principles of religious moderation in the Qur'an. Assimellereng serves as a bridge to build understanding and cooperation among religious communities, as well as to maintain harmony and brotherhood amidst diversity. This research provides a significant contribution to strengthening religious moderation in the Bugis community.